Gene flow, ancient polymorphism, and ecological adaptation shape the genomic landscape of divergence among Darwin's finches - Han, Fan; Lamichhaney, Sangeet; Grant, B. Rosemary; Grant, Peter R.; Andersson, Leif; Webster, Matthew T.

(untitled) (Genome Research, 2017)
Genomic comparisons of closely related species have identified “islands” of locally elevated sequence divergence. Genomic islands may contain functional variants involved in local adaptation or reproductive isolation and may therefore play an important role in the speciation process. However, genomic islands can also arise through evolutionary processes unrelated to speciation, and examination of their properties can illuminate how new species evolve. Here, we performed scans for regions of high relative divergence (FST) in 12 species pairs of Darwin's finches at different genetic distances. In each pair, we identify genomic islands that are, on average, elevated in both relative divergence (FST) and absolute divergence (dXY). This signal indicates that haplotypes within these genomic regions became isolated from each other earlier than the rest of the genome. Interestingly, similar numbers of genomic islands of elevated dXY are observed in sympatric and allopatric species pairs, suggesting that recent gene flow is not a major factor in their formation. We find that two of the most pronounced genomic islands contain the ALX1 and HMGA2 loci, which are associated with variation in beak shape and size, respectively, suggesting that they are involved in ecological adaptation. A subset of genomic island regions, including these loci, appears to represent anciently diverged haplotypes that evolved early during the radiation of Darwin's finches. Comparative genomics data indicate that these loci, and genomic islands in general, have exceptionally low recombination rates, which may play a role in their establishment.